A conservative treatment of patent ductus arteriosus in very low birth weight infants. (January 2017) - Letshwiti, J.B.; Semberova, J.; Pichova, K.; Dempsey, E.M.; Franklin, O.M.; Miletin, J.
Abstract: Background: Treatment of the patent ductus arteriosus (PDA) in the preterm infant remains contentious. There are numerous options of the PDA management from early targeted treatment, late (symptomatic) treatment to no treatment at all. Aims: To evaluate a three different PDA management approaches in very low birth weight (VLBW) infants. Study design: A retrospective observational time series study of three cohorts of VLBW infants born between 2004 and 2011. Subjects: Infants in Symptomatic Treatment Group (STG) were echocardiographically evaluated when clinical signs suggestive of a PDA were present and treated if a haemodynamically significant PDA was confirmed. Early Targeted Group (ETG) underwent echocardiography within the first 48 h and infants received ibuprofen if a large PDA was present. Conservative Treatment Group (CTG) was screened by echocardiography on day seven of life; patients with PDA were managed with increased positive end expiratory pressure and fluid restriction as a first line intervention. Outcomes: The primary outcome was medical and surgical treatment in the three time periods. Secondary outcomes included mortality, severe periventricular and intraventricular haemorrhage, respiratory distress syndrome and chronic lung disease. Results: There were 138 infants diagnosed with PDA; 52 infants in STG, 52 infants in ETG and 34 infants in CTG. Ibuprofen therapy and ligation were less frequent in CTG. There was significantly decreased incidence of chronic lung disease in CTG compared to STG (18% vs. 51%; p = 0.003) and to ETG (18% vs. 46%; p = 0.02). There was no difference in the other short term outcomes. Conclusion: Conservative treatment of persistent ductus arteriosus in VLBW infants is a feasible option and future randomized trials of conservative management are warranted. Highlights: Management of patent ductus arteriosus in very low birth weight infants remains controversial. Minimally invasive approach trying to avoid medical and surgical treatment seems to be feasible option. Infants receiving minimally invasive management had the lowest rate of chronic lung disease.